Investigation on fatigue life enhancement of S460G2+M using semi-automated GMAW and HFMI/PIT / Dahia Andud - Andud, Dahia (2019)
Welding is a well-known method for joining various steel structures such as bridges, cranes, pipes and oil and gas platforms. Although numerous weld discontinuities might occur that can damage steel structures, many manufacturers still favour this method because of versatility and cost-effectiveness. Welding responsible for almost 90% of mechanical engineering fatigue failures since welding is always associated with various defects which sources of stress concentration where the location of the fatigue crack initiation. This research focused on the fatigue life investigation of the Butt weld, Transverse and Longitudinal T-joint welds of offshore steel S460G2+M with special attention on enhancing the fatigue life of welded structure using a new device of high-frequency mechanical impact using a pneumatic system (HFMI/PIT). In the first phase of the investigation, identification of the best welding parameters combination of the semi-automated GMAW process conducted by developing the Welding Procedure Specification (WPS) for the offshore steel S460G2+M following AWS D1.1 Section 4. WPS is a formal written document describing welding procedures and providing directions to the welder for making sound and excellent quality of welds. The second phase focused on the welding preparation of the fatigue test specimens followed by fatigue testing under a constant amplitude loading and all the fatigue data evaluated based on the International Institute of Welding (IIW) commission XIII. Some of the fatigue specimens were treated with HFMI/PIT for fatigue life enhancement. The third phase dealt with fatigue assessment of the as-welded Longitudinal T-joint welds based on the effective notch stress approach (ENS) using finite element software MSC Marc/Mentat. Based on this research, the development of the actual WPS for the offshore steel S460g2+M depends on the results of the destructive and non-destructive tests reported in PQR. After all testing results complied with the fabrication standard requirements, the actual WPS is to be established. A non-certified welder who has experienced in welding works is assigned to produce high-quality weld based on the welding parameters in actual WPS. It can be concluded that the most exceptional fatigue life of the untreated and HFMI/PIT specimen of the offshore steel S460G2+M is Transverse T-joint welds, followed by Longitudinal T-joint weld and Butt weld. The HFMI/PIT treatment shifted the fatigue crack initiation from the weld toe to the base metal region as the results of the elimination of stress concentration and conversion of the tensile residual stress to compressive residual stress which increased the fatigue life of the welded joint. The FAT class of the converted experiment fatigue data to ENS approach shows good agreement with the FAT class of the ENS fatigue assessment for Longitudinal T-joint weld because both FAT classes inferior to the FAT class recommendation of the IIW commission XIII for the ENS fatigue assessment. The single design S-N curve of FAT 225 of the IIW commission XIII for the ENS approach is relevant for the fatigue assessment of Longitudinal T-joint weld using the ENS approach.